Validity of the inexpensive Stepping Meter in counting steps in free living conditions: a pilot study. Issue 8 (21st June 2006) - De Cocker, K; Cardon, G; De Bourdeaudhuij, I
Abstract : Objectives: To evaluate if inexpensive Stepping Meters are valid in counting steps in adults in free living conditions. Methods: For six days, 35 healthy volunteers wore a criterion Yamax Digiwalker and five Stepping Meters every day until all 973 pedometers had been tested. Steps were recorded daily, and the differences between counts from the Digiwalker and the Stepping Meter were expressed as a percentage of the valid value of the Digiwalker step counts. The criterion used to determine if a Stepping Meter was valid was a maximum deviation of 10% from the Digiwalker step counts. Results: A total of 252 (25.9%) Stepping Meters met the criterion, whereas 74.1% made an overestimation or underestimation of more than 10%. In more than one third (36.6%) of the invalid Stepping Meters, the deviation was greater than 50%. Most (64.8%) of the invalid pedometers overestimated the actual steps taken. Conclusions: Inexpensive Stepping Meters cannot be used in community interventions as they will give participants the wrong message.